The association between visceral adiposity index and decreased renal function: A population-based study - Qin, Zheng; Chen, Xinyang; Sun, Jiantong; Jiang, Luojia (Frontiers in Nutrition, 2023)
Aims: We aimed to investigate the association of visceral adiposity index (VAI) with decreased renal function in US adults. Design and Methods: Cross-sectional data were analyzed for 35018 adults in the National Health and Nutrition Examination Survey (NHANES) 2005-2018. VAI was determined using waist circumference, body mass index, triglycerides and high-density lipoprotein-cholesterol. Albuminuria was defined as urinary albumin-to-creatinine ratio > 30mg/g. A low estimated-glomerular filtration rate (eGFR) was defined as an eGFR lower than 60 ml/min/1.73 m2. Chronic kidney disease (CKD) was defined as either albuminuria or low-eGFR. A multivariable logistic regression analysis was utilized to explore the relationship of VAI with albuminuria, low-eGFR and CKD. Subgroup analysis and interaction tests were also conducted. Results: A total of 35018 participants were enrolled with albuminuria, low-eGFR, and CKD prevalence rates of 5.18%, 6.42%, and 10.62%, respectively, which increased with the higher VAI tertiles. After full adjustment, a positive association of VAI with albuminuria (OR= 1.03, 95% CI: 1.00, 1.06) and CKD (OR=1.04, 95% CI:1.02, 1.06) was observed. Participants in the highest VAI tertile had a significantly 30% increased risk for albuminuria (OR=1.30, 95% CI: 1.07, 1.58) and a 27% increased risk for CKD (OR=1.27, 95% CI: 1.08, 1.49) compared with those in the lowest VAI tertile. No statistically significant association between VAI and low-eGFR was detected. Subgroup analysis and the interaction term indicated that there was no significant difference among different stratifications. Conclusion: Visceral adiposity accumulation evaluating by VAI was associated with increased likelihood of the decline in renal function.